Disney Mickey Mouse Clubhouse - DiCicco, Sue; Disney Storybook Artists; Disney Channel (Firm); Playhouse Disney (Firm) (Lincolnwood, Ill. : Publications International, 2008)
Challenges readers to find specific items in color spreads featuring Mickey Mouse and his clubhouse friends.
Cover title.
On board pages, with padded cover.
"On Disney Channel"--Cover.
1.8
K-3
K-3
Keywords: Picture puzzles -- Juvenile literature; Literary recreations -- Juvenile literature; Mickey Mouse (Fictitious character) -- Juvenile literature; Disney characters -- Juvenile literature; Picture puzzles; Literary recreations; Mickey Mouse (Fictitious character); Disney characters; Picture puzzles; Literary recreations; Mickey Mouse (Fictional character); Disney characters; Picture books for children